This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The summation formulas for the first several powers of k are
k = 1 ∑ n k k = 1 ∑ n k 2 k = 1 ∑ n k 3 k = 1 ∑ n k 4 k = 1 ∑ n k 5 = 2 n ( n + 1 ) = 2 n 2 + 2 n = 6 n ( n + 1 ) ( 2 n + 1 ) = 3 n 3 + 2 n 2 + 6 n = 4 n 2 ( n + 1 ) 2 = 4 n 4 + 2 n 3 + 4 n 2 = 3 0 n ( n + 1 ) ( 2 n + 1 ) ( 3 n 2 + 3 n + 1 ) = 5 n 5 + 2 n 4 + 3 n 3 − 3 0 n = 1 2 n 2 ( n + 1 ) 2 ( 2 n 2 + 2 n − 1 ) = 6 n 6 + 2 n 5 + 1 2 5 n 4 − 1 2 n 2
From the above we notice that the first two terms in the formula for k = 1 ∑ n k a appear to be a + 1 k a + 1 + 2 k a , and the remaining terms are O ( k a − 1 ) .
This is indeed the case, which can be proven with Faulhaber's formula, written about in the wiki Sum of n, n², or n³ .
Armed with this result, we tackle the given limit:
n → ∞ lim n 2 0 1 8 1 2 0 1 8 + 2 2 0 1 8 + 3 2 0 1 8 + . . . . + n 2 0 1 8 − 2 0 1 9 n = n → ∞ lim n 2 0 1 8 2 0 1 9 n 2 0 1 9 + 2 n 2 0 1 8 + O ( n 2 0 1 7 ) − 2 0 1 9 n = n → ∞ lim ( 2 0 1 9 n + 2 1 + O ( n 1 ) ) − 2 0 1 9 n = 2 1
Problem Loading...
Note Loading...
Set Loading...
n → ∞ lim n 2 0 1 8 1 2 0 1 8 + 2 2 0 1 8 + ⋯ n 2 0 1 8 − 2 0 1 9 n = n → ∞ lim 2 0 1 9 n 2 0 1 8 2 0 1 9 ( 1 2 0 1 8 + 2 2 0 1 8 + ⋯ + n 2 0 1 8 ) − n 2 0 1 9 = ∞ ∞ Let a n = 2 0 1 9 ( 1 2 0 1 8 + 2 2 0 1 8 + ⋯ + n 2 0 1 8 ) − n 2 0 1 9 and b n = 2 0 1 9 n 2 0 1 8 . To evalute the limit we apply Stolz-Cesàro Theorem 1 . Then n → ∞ lim b n a n = n → ∞ lim b n + 1 − b n a n + 1 − a n = n → ∞ lim 2 0 1 9 ( n + 1 ) 2 0 1 8 − 2 0 1 9 n 2 0 1 8 2 0 1 9 ( n + 1 ) 2 0 1 8 − ( n + 1 ) 2 0 1 9 + n 2 0 1 9 n → ∞ lim b n a n = 2 1
Note: L L L = n → ∞ lim 2 0 1 9 m = 0 ∑ 2 0 1 8 ( m 2 0 1 8 ) n 2 0 1 8 − m − 2 0 1 9 n 2 0 1 8 2 0 1 9 r = 0 ∑ 2 0 1 8 ( r 2 0 1 8 ) n 2 0 1 8 − r + n 2 0 1 9 − k = 0 ∑ 2 0 1 9 ( k 2 0 1 9 ) n 2 0 1 9 − k = n → ∞ lim 2 0 1 9 ( n 2 0 1 8 + 2 0 1 8 n 2 0 1 7 + 2 ! . 2 0 1 6 ! 2 0 1 8 ! n 2 0 1 6 + ⋯ + 1 ) − 2 0 1 9 n 2 0 1 8 2 0 1 9 ( n 2 0 1 8 + 2 0 1 8 n 2 0 1 7 + 2 ! . 2 0 1 6 ! 2 0 1 8 ! n 2 0 1 6 + ⋯ + 1 ) + n 2 0 1 9 − ( n 2 0 1 9 + 2 0 1 9 n 2 0 1 8 + 2 ! . 2 0 1 7 ! 2 0 1 9 ! n 2 0 1 7 + ⋯ + 1 ) = n → ∞ lim 2 0 1 9 . 2 0 1 8 n 2 0 1 7 + 2 ! . 2 0 1 7 ! 2 0 1 8 ! n 2 0 1 6 + ⋯ + 1 2 0 1 8 . 2 0 1 9 n 2 0 1 7 + ⋯ + 2 0 1 9 − 2 ! . 2 0 1 7 ! 2 0 1 9 ! n 2 0 1 7 − ⋯ − 1 = 2 0 1 9 . 2 0 1 8 2 0 1 9 . 2 0 1 8 − 2 ! . 2 0 1 7 ! 2 0 1 9 ! = 2 0 1 9 . 2 0 1 8 2 0 1 9 . 2 0 1 8 ( 1 − 2 1 ) = 2 1